2022
DOI: 10.1038/s41541-022-00469-x
|View full text |Cite
|
Sign up to set email alerts
|

A DNA vaccine targeting VEE virus delivered by needle-free jet-injection protects macaques against aerosol challenge

Abstract: We have previously shown that DNA vaccines expressing codon optimized alphavirus envelope glycoprotein genes protect both mice and nonhuman primates from viral challenge when delivered by particle-mediated epidermal delivery (PMED) or intramuscular (IM) electroporation (EP). Another technology with fewer logistical drawbacks is disposable syringe jet injection (DSJI) devices developed by PharmaJet, Inc. These needle-free jet injection systems are spring-powered and capable of delivering vaccines either IM or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…These results concur with other studies that have shown the immunogenicity of DNA vaccines to be enhanced with PharmaJet Stratis delivery as compared to needle and syringe [ 36 , 37 , 38 , 47 , 48 ]. This study also demonstrated significant improvement in the antibody responses with the MVA vaccine delivered using this device.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results concur with other studies that have shown the immunogenicity of DNA vaccines to be enhanced with PharmaJet Stratis delivery as compared to needle and syringe [ 36 , 37 , 38 , 47 , 48 ]. This study also demonstrated significant improvement in the antibody responses with the MVA vaccine delivered using this device.…”
Section: Discussionsupporting
confidence: 92%
“…The needle-free jet injection developed by PharmaJet, Inc. can deliver vaccines using a narrow, precise fluid stream, which is an improvement over the standard needle and syringe [ 38 ]. The PharmaJet Stratis needle-free injection device improved immune responses to the DNA vaccine, with six of the ten rabbits having binding antibody responses after the second DNA vaccination, whereas none of the rabbits that received the DNA vaccines via needle injection developed binding antibody responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dr. Hooper’s group at USAMRIID tested their pWRG/VEE plasmid DNA vaccine in NHP delivered via Tropis ID or Stratis IM and compared immunogenicity and protection from viral challenge ( Table 3 ) [ 94 ]. Vaccinated animals showed significant protection from infection and although IM delivery induced more potent immune responses, animals in the ID group showed better protection from challenge.…”
Section: Nfis Delivery Of Dna Vaccines For Emerging Infectious Diseasesmentioning
confidence: 99%
“…A candidate vaccine is the V3526, even if it protects against only a few genotypes of VEEv [ 671 ]. For these reasons, the research has always continued over the years with a different approach, as DNA vaccines have proven particularly effective at eliciting protective immune responses in animal models [ 672 , 673 ]. Laboratory workers at USAMRIID are currently immunized with live (TC-83) and killed (C-84) vaccines.…”
Section: Biological Agents For Bio-warfare/bioterrorism Category A–bmentioning
confidence: 99%